MAKNA PENDIDIKAN FORMAL BAGI PETANI (Studi Tentang Anak Putus Sekolah Di Kelurahan Sungai Perak Kecamatan Tembilahan Kabupaten Indragiri Hilir) - Aprianis "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study was conducted in Sungai Perak Sub-district Tembilahan in Indragiri Hilir. This research was conducted to obtain information about the meaning of formal education for farmers with the purpose of knowing the cause of school dropouts and parental views of school dropouts in Sungai Perak village. The theory of Hasbunallah is the theory of education and Mutrofin theory of the cause of school dropouts. This research is a research survey using qualitative descriptive methods, data collection by means of interviews, observations, and documentation. The number of informant in this study was 9 persons consisting of 1 person Secretary Lurah, 4 parents who dropped out of school and 4 children who dropped out of school. The results showed that the causes of dropouts are divided into two namely internal causes, namely the inability to follow the learning and low interest of children to attend school while the external cause of the family economic condition, Parental and environmental concerns. The farmer's view of the child's formal education is very low, as many factors cause them to assume that education is less important and costs only quite a lot. Keywords: Meaning of education, causes and dropouts